2008
DOI: 10.1124/jpet.108.146084
|View full text |Cite
|
Sign up to set email alerts
|

The Modulation of Synaptic GABAA Receptors in the Thalamus by Eszopiclone and Zolpidem

Abstract: Eszopiclone (Lunesta; Sepracor, Marlborough, MA) and zolpidem [N,N,6-trimethyl-2-(4-methylphenyl)-imidazo(1,2-a)pyridine-3-acetamide] are among the most commonly prescribed hypnotics in use in the United States. The thalamus plays a pivotal role in sleep regulation and rhythmicity. Two distinct subtypes of synaptic GABA A receptors (GABA A -Rs), ␣ 1 ␤ 2 ␥ 2 and ␣ 3 ␤ 3 ␥ 2 , are expressed in thalamocortical relay neurons and in interneurons of the RTN (reticular thalamic nucleus), respectively. Thalamocortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 31 publications
(67 reference statements)
0
39
0
Order By: Relevance
“…In a small preliminary study, eszopiclone, which acts on γ-aminobutyric acid (GABA)-ergic neurons in the TRN 73 , significantly increased spindles in schizophrenia but not sleep-dependent memory 30 . In another study that did not include PSG, longerterm administration of eszopiclone improved working memory in schizophrenia, but not symptoms 74 .…”
Section: Discussionmentioning
confidence: 99%
“…In a small preliminary study, eszopiclone, which acts on γ-aminobutyric acid (GABA)-ergic neurons in the TRN 73 , significantly increased spindles in schizophrenia but not sleep-dependent memory 30 . In another study that did not include PSG, longerterm administration of eszopiclone improved working memory in schizophrenia, but not symptoms 74 .…”
Section: Discussionmentioning
confidence: 99%
“…To isolate the effects of picrotoxin at GlyRs, picrotoxin was applied concurrently with the GABA A R-specific antagonist gabazine, as has been done previously (41). While it has been suggested that gabazine is unable to unmask tonic GABA A R-mediated currents, we have previously used this concentration to reveal tonic GABA A R conductance in the thalamus (42). Here, we found that applications of picrotoxin in combination with gabazine produced significant shifts in the holding currents of MSNs (Fig.…”
Section: Demonstration Of Exogenously Activated Glyr Currents In Varimentioning
confidence: 99%
“…Their molecular mechanisms of action have never been investigated in detail. The little information currently available suggests that zolpidem is a more potent modulator than eszopiclone of currents mediated by native α1β2γ2 GABAA receptors in mouse thalamocortical relay neurons (Jia et al, 2009). However, in recombinant α1β2γ2 GABAA receptors expressed in Xenopus laevis oocytes, estimates of the apparent affinities of the two drugs were similar, at 50-60 nM (Hanson et al, 2008).…”
Section: Introductionmentioning
confidence: 89%
“…This later effect could be because GABA release at some synapses is sub-saturating. As zolpidem and eszopiclone appear to achieve these effects via identical mechanisms and similar potencies at the α1β2γ2 GABAA receptors, their differing therapeutic profiles must be due to either different pharmacological effects at other CNS receptors (Jia et al, 2009;Nutt and Stahl, 2010), or to different pharmacokinetic or distribution profiles.…”
Section: Discussionmentioning
confidence: 99%